EMG signals characterization in three states of contraction by a fuzzy network and feature extraction - Mokhlesabadifarahani, Bita; Gunjan, Vinit Kumar; SpringerLink (Online service). (Singapore Springer Singapore, 2015)
Neuro-muscular and musculoskeletal disorders and injuries highly affect the lifestyle and the motion abilities of an individual. This brief highlights a systematic method for detection of the level of muscle power declining in musculoskeletal and Neuro-muscular disorders. The neuro-fuzzy system is trained with 70 percent of the recorded Electromyography (EMG) cut off the window and then used for classification and modeling purposes. The neuro-fuzzy classifier is validated in comparison to some other well-known classifiers in the classification of the recorded EMG signals with the three states of contractions corresponding to the extracted features. Different structures of the neuro-fuzzy classifier are also comparatively analyzed to find the optimum structure of the classifier used.
Introduction to EMG Technique and Feature Extraction -- Methodology for working with EMG dataset -- Results -- Conclusions and Inferences of Present Study.
Electronic reproduction.
Keywords: Signal processing -- Digital techniques; Fuzzy systems; Electronic books